2006
DOI: 10.1002/bit.20744
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of human metabolites of propranolol using laboratory‐evolved bacterial cytochromes P450

Abstract: Testing the toxicities and biological activities of the human metabolites of drugs is important for development of safe and effective pharmaceuticals. Producing these metabolites using human cytochrome P450s is difficult, however, because the human enzymes are costly, poorly stable, and slow. We have used directed evolution to generate variants of P450 BM3 from Bacillus megaterium that function via the "peroxide shunt" pathway, using hydrogen peroxide in place of the reductase domain, oxygen and NADPH. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
111
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 37 publications
0
111
0
Order By: Relevance
“…This progress can directly be of use for efficient and timesaving production of human drug metabolites. High yields and conversion rates can already be achieved by using corresponding human (Rushmore et al, 2000;Vail et al, 2005;Schroer et al, 2010;Geier et al, 2012;Schiffer et al, 2015) or suitable nonhuman (Taylor et al, 1999;Otey et al, 2006;Sawayama et al, 2009;Reinen et al, 2011;Di Nardo and Gilardi, 2012;Kiss et al, 2015;Ren et al, 2015) P450 enzymes in a whole-cell system to produce respective metabolites. The majority of published bacterial P450 enzymes used for the conversion of drugs are mutants of CYP102A1 (BM3) from Bacillus megaterium.…”
Section: Discussionmentioning
confidence: 99%
“…This progress can directly be of use for efficient and timesaving production of human drug metabolites. High yields and conversion rates can already be achieved by using corresponding human (Rushmore et al, 2000;Vail et al, 2005;Schroer et al, 2010;Geier et al, 2012;Schiffer et al, 2015) or suitable nonhuman (Taylor et al, 1999;Otey et al, 2006;Sawayama et al, 2009;Reinen et al, 2011;Di Nardo and Gilardi, 2012;Kiss et al, 2015;Ren et al, 2015) P450 enzymes in a whole-cell system to produce respective metabolites. The majority of published bacterial P450 enzymes used for the conversion of drugs are mutants of CYP102A1 (BM3) from Bacillus megaterium.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious route is to use isolated human P450s, but these complex multiprotein systems are membrane-bound, poorly stable, cofactor-dependent, and generally exhibit low reaction rates [7,8]. More promising results have been reported for laboratory-evolved bacterial P450s, which are capable of catalyzing the H 2 O 2 -dependent hydroxylation of pharmaceuticals via the "peroxide shunt" pathway [9]. Recent studies, however, have demonstrated that this approach needs further optimization [10].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to evolve the cyclization specificity of the Thermoanerobacterium thermosulfurigenes strain EM1 (Tabium) CGTase into R-amylase like hydrolytic activity on starch, we separately applied error-prone PCR (epPCR) and saturated mutagenesis, also evaluating the effectiveness of directed evolution techniques for interconversion of reaction specificities. Directed evolution has emerged as a powerful method for the creation of proteins with altered properties, e.g., tighter binding, resistance to denaturing conditions, and modified and/or improved reaction specificities (8)(9)(10)(11)(12)(13). Several directed evolution methods are commonly used nowadays, epPCR, DNA shuffling, site-saturation mutagenesis, etc., in the generation of genetic diversity, as reviewed (14,15).…”
mentioning
confidence: 99%